Use of GFR equations to adjust drug doses in an elderly multi-ethnic group—a cautionary tale - Gill, Jagbir; Malyuk, Rhonda; Djurdjev, Ognjenka; Levin, Adeera (Nephrology, dialysis, transplantation, 2007)
Background. Glomerular filtration rate (GFR) is the best index of kidney function. Mathematical estimations of GFR, based on serum creatinine (SCr), are a clinically useful method to follow renal function, but have certain limitations which need to be considered. Convention supports the use of Cockcroft–Gault (CG) for the purposes of drug dosing. The impact of using the modification of diet in renal disease (MDRD) formula has not been formally evaluated with respect to drug dosing; especially in an elderly multi-ethnic population. A cross-sectional study of long-term care facility patients was conducted to demonstrate the impact of the use of different formulae in the elderly for the purposes of medication dosing. Methods. Patients with ESRD were excluded. GFR was calculated for all subjects using the four-variable modified MDRD equation (re-expressed using isotope-dilution mass spectrometry-based creatinine values) and the CG equation (corrected for body surface area). Discordance was defined as a reclassification of one stage of chronic kidney disease (CKD) by using a different formula. Calculated GFR from each formula was used to calculate the doses of two drugs: amantadine and digoxin, to demonstrate the potential impact of the use of different formulae on the risk of drug toxicity. Results. A total of 180 patients were identified with a mean age of 85 years, of which 30% were Asian. Mean MDRD-GFR and CG-GFR in the same group were different (72.9 ml/min/1.73 m2 vs 52.1 ml/min/1.73 m2). Only 37.2% of the patients were categorized in the same stage of CKD by both methods. When MDRD was used in place of CG to determine drug dose adjustments, we found that 20% fewer patients would have qualified for a dose reduction of amantadine, which would have translated to a higher total cumulative dose delivered. Conclusions. The use of CG and MDRD provided discordant estimations in over 60% of the elderly patients. While the importance of these equations cannot be questioned, caution should be exercised in situations where they have not been prospectively validated. Therefore, their interchangeable use cannot be advocated in the dosing of medications until further prospective validations are performed.